2379. Multicenter Evaluation of Ceftazidime–Avibactam for Multidrug-Resistant Gram-Negative Bacterial Infections. (26th November 2018) - Jorgensen, Sarah; Trinh, Trang D; Zasowski, Evan J; Lagnf, Abdalhamid M; Bhatia, Sahil; Simon, Samuel; Estrada, Sandy; Rosenberg, Joshua; Steed, Molly; Davis, Susan L; Rybak, Michael J
Abstract: Background: The increasing prevalence of multidrug-resistant (MDR) Gram-negative bacteria (GNB) represents an urgent public health threat. Ceftazidime–avibactam (CZA) is a novel cephalosporin/β-lactamase inhibitor with activity against MDR GNB including carbapenem-resistant Enterobacteriaceae (CRE). Real-world experience with CZA in the treatment of MDR GNB is accumulating but remains limited by the small number of patients thus far described. We sought to build upon prior reports by describing the clinical characteristics and outcomes of a diverse cohort of patients with MDR GNB infections treated with CZA. Methods: Retrospective, multicenter, cohort study of patients treated with CZA (≥72 h) for suspected or confirmed MDR GNB (resistant to ≥1 antibiotic in ≥3 classes) infections between 2015 and 2018. The primary outcome was clinical failure defined as a composite of 30-day mortality, 30-day recurrence, or worsening signs and symptoms while on CZA. Independent predictors of clinical failure were sought through multivariable logistic regression analysis. Results: A total of 114 patients were included. The median (IQR) age was 65 (53, 74), the median Charlson Comorbidity Index was 4 (2, 6), and the median APACHE II score was 20 (14, 28). CRE and MDR Pseudomonas aeruginosa were isolated in 74 (66%) and 31 (28%) of cases, respectively. The predominant sources were respiratory (40%) and urinary tract (20%). Blood cultures were positive in 10% of cases. Combination therapy (≥48 h) was used in 40%. Among carbapenem-resistant Klebsiella pneumoniae ( n = 34), 97% were susceptible to CZA. The resistant isolate was positive for NDM and OXA. Clinical failure, 30-day mortality, and recurrence were 28%, 13% and 5%, respectively. Independent predictors of clinical failure were immune compromise ( a OR 6.25, 95% CI 1.30, 30.11), Glasgow Coma scale ≤ 12 ( a OR 3.76, 95% CI 1.30, 10.88), primary bacteremia or respiratory source ( a OR 2.96, 1.07–8.17) and age less than 65 ( a OR 2.87, 95% CI 1.09, 7.61). Conclusion: The use of CZA was associated with a clinical failure rate of 28% which compares favorably with historical controls of MDR GNB infections. Future investigations evaluating long-term outcomes and comparative studies are needed to more precisely define the role of CZA in MDR GNB infections. Disclosures: S. L. Davis, Achaogen: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. Melinta: Scientific Advisor, Consulting fee. Nabriva: Scientific Advisor, Consulting fee. Zavante: Scientific Advisor, Consulting fee. M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support. Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support.